Nucleotide sequence of the primer RNA for DNA replication of filamentous bacteriophages. - Higashitani, N (1993)
We determined the nucleotide sequence of RNA synthesized in vitro by Escherichia coli RNA polymerase at the complementary-strand replication origin on the single-stranded viral DNA of bacteriophages f1 and IKe (ori-RNA) by using chain-terminating ribonucleoside triphosphate analogs. The results indicated that the start site of f1 ori-RNA synthesis is 20 nucleotides downstream from the site previously reported (K. Geider, E. Beck, and H. Schaller, Proc. Natl. Acad. Sci. USA 75:645-649, 1978) and that the RNA sequence [(5')pppAGGGCGAUGGCCCACUACGU-OH(3')] is complementary to the f1 DNA sequence from nucleotides 5736 to 5717, with minor heterogeneity at the 3' end. IKe ori-RNA had a sequence identical to that of f1 ori-RNA, except for a single base substitution, and IKe RNA was complementary to a region of IKe DNA (from nucleotides 6441 to 6422) that was homologous to the f1 sequence. Phenotypes and ori-RNA sequences in the relevant region of the genome of f1 deletion mutants were consistent with the presently determined sequence of ori-RNA. A possibility that ori-RNA synthesis is initiated by a mechanism similar to that for general transcription is suggested as a result of the new assignment of the ori-RNA start site. The double-origin plasmid assay of minus-strand origin activity, a sensitive in vivo method for detecting cis-acting elements for the initiation of DNA replication on a single-stranded DNA template, is described.